A probabilistic approach to assessment of the quality of drinking water - Wątor, Katarzyna; Kmiecik, Ewa; Postawa, Adam; Rusiniak, Piotr (Geologos, 2019)
Knowledge of uncertainty in analytical results is of prime importance in assessments of compliance with requirements set out for the quality of water intended for human consumption. Assessments of drinking water quality can be performed using either a deterministic or a probabilistic method. In the former approach, every single result is referred directly to the parametric value, while in the probabilistic method uncertainty related to analytical results is taken into account during the decision-making process. In the present research, laboratory uncertainty and uncertainty determined on the basis of results of analyses of duplicate samples collected in two Polish cities were compared and used in the probabilistic approach of water quality assessment. Using the probabilistic method, more results were considered to be “above the parametric value”. Most excesses were observed when the maximum allowable uncertainty as set out in the Regulation of the Minister of Health of 7 December 2017 was used, which is due to the highest values of these uncertainties. The lowest values above parametric values in the probabilistic approach were observed when measurement uncertainty was considered.